Shifting the goalposts? Analysing changes to performance peer groups used to determine the remuneration of FTSE100 CEOs - Skovoroda, Rodion; Bruce, Alistair (Wiley, 2017)
This paper examines year-on-year changes to the composition of performance peer groups used for Relative Performance Evaluation (RPE) in setting CEO pay in FTSE 100 companies and finds evidence of peer selection bias. We find that firms keep their peer groups weak by excluding relatively stronger performing peers. We also show that peer selection bias is less pronounced in firms with higher institutional investor ownership, which suggests that institutional investors might be aware of the risks of peer selection bias. The results suggest that peer group modifications can be viewed, at least in part, as an expression of managerial rent-seeking.